PARADIGMA LITERALISTIK DALAM PENALARAN HUKUM ISLAM - Achmad Musyahid Idrus (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2020)
The literalistic paradigm or classical Islamic law paradigm with a discussion of the style of Arabic texts both in terms of grammar and syntax that tends to ignore the discussion about the basic intentions of the revelation that is behind the literal text. Simply put, the literalist paradigm rests on the text both directly and indirectly. In the tradition of literalistic reasoning, there are two ways to get knowledge from the text, which are to hold the zahir text and to hold the intention of the text, not the zahir text. Sticking to the zahir text and the intent of the non-zahir text is characteristic of the reasoning process in Islamic law to draw a conclusion in the form of knowledge. Reasoning in Islamic law aims to produce knowledge that is associated with thinking and not with curiosity. However, not all thinking activities can be said as reasoning because reasoning is a thought activity that has certain characteristics in finding the truth.